Application Of Palm Oil And Palm Kernel Oil In Producing Non-Dairy Whipping Cream - Shamsi, Kambis (2003)
Refined, bleached and deodorized palm kernel oil (RBDPKO) and refined, bleached and deodorized palm oil (RBDPO), sucrose, corn syrup solids, sodium caseinate, soybean lecithin , carboxymethylcellulose (CMC), monoacylglycerol and distilled water were blended and made into creams. The creams were measured in terms of fatty acid composition (FAC), stability, slip melting point (SMP), iodine value (IV), whipping test, overrun, viscosity and solid fat content (SFC) . Differential scanning calorimetry (DSC) and X-ray diffractometry (XRD) were used to study the crystal structure of the creams. The results showed that the increase in unsaturated fatty acids (UFA) , among which oleic acid was the most prominent, could produce a more stable foam in palm oil-based whipping cream. It was shown that increasing the IV had an increasing effect on the stability of foam in non-dairy whipping cream as well . This study showed the advantages of a palm oil-based whipping cream over commercial dairy whipping cream (DWC) particularly when the stability of the foam is being considered and the product is destined to be consumed in hot weather. It was shown that the percentage of fat in whipping cream, whether dairy or non-dairy, was not the only determining factor for producing a stable foam , but the composition of the component fat must be taken into account as well. It was also found that the IV was highly correlated with overrun and SFC and the increase in the degree of unsaturation can lead to the raising of overrun . However, there was no correlation between IV and the trend of viscosity in the creams as viscosity is mostly under the influence of stabilisers and emulsifiers, rather than the degree of unsaturation in fatty acids (FA) Viscosity acted as an independent variable of SFC as well . The studies using OSC and XRD on palm oil-based whipping cream developed showed that all blends possessed a stable and shiny B polymorph at 25°C, which stands RBOPO and RBDP KO in an advantage for application in a non-dairy whipping cream. Some eutectic effects were also observed in some blends, which could be attributed to complex combination of triacylglycerol (TAG) in RBDPO and RBDPKO. It was also found that addition of RBOPO and RBDP KO to OWC could increase its stability and consistency in hot weather.